BULGARIAN REVOLT OF 1876 IN THE UK PARLIAMENTARY RECORDS - Yahya BAĞÇECİ (Fırat University, 2019)
In May 1876, some Bulgarians revolted by the incitement of Russia. Purpose of the rebels was to separate Bulgarians from the Ottoman Empire. They first began to attack Turks and Muslims and slaughter them by all kinds of tortures. Because there was not sufficient soldiers in the region and because the Sublime Porte did not take the necessary measures immediately, the Muslim community formed voluntary troops in order to defend themselves. Failing to get the support of large masses, the rebellion was suppressed by a dispatch of military troops to the region. This uprising, which could actually be described as a small riot, was soon rendered a pretext for a big campaign started against Turks. This campaign began firstly by the publication of a news report in the Daily News, the leading Liberal media organ, which claimed that Bulgarians including women and children were being slaughtered by Turks. This was followed by other reports that accused Turks of grave crimes. The matter was then taken by the Liberal Party to the UK Parliament. The Liberal Party brought to the parliamentary agenda all kinds of allegations made by newspapers against Turks and accused the Disraeli Government of remaining insensitive to the allegations of massacre. The Prime Minister Benjamin Disraeli, on the other hand, denied the allegations by sharing official information. The agitation campaign, however, continued increasingly and the former leader of the Liberal Party, William Ewart Gladstone, became the head of the campaign. Gladstone’s aim was to come to the power again by taking down the President Disraeli, who he accused of following pro-Turkish policies.